Aspectos de la biología reproductiva del Picaflor Verde Común (Chlorostilbon aureoventris) - Fraga, Rosendo Manuel (1984)
An incubation period of 15 days and a nestling period of 21-23 days were recorded for the hummingbird Chlorostilbon aureoventris. Data on nestling weight and growth are inc1uded. In a nest visited by 2 fema1es, 3 nestlings were successfully reared.